2023
DOI: 10.1038/s41598-023-30444-y
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles induce oxidative stress, genotoxicity, and apoptosis in the hemocytes of Bombyx mori larvae

Abstract: The expanded uses of zinc oxide nanoparticles (ZnO-NPs) have grown rapidly in the field of nanotechnology. Thus, the increased production of nanoparticles (NPs) increases the potential risks to the environment and occupationally exposed humans. Hence, safety and toxicity assessment including genotoxicity of these NPs is indispensable. In the present study, we have evaluated the genotoxic effect of ZnO-NPs on 5th larval instar of Bombyx mori after feeding on mulberry leaves treated with ZnO-NPs at concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Another study in 2012, explored the neuroprotective effects of ZnO NP on spatial cognition and synaptic plasticity in mice with depressive-like behaviors 32 . It is important to keep in mind that most of the research has shown conflicting findings to ours as most of the results showed the ZnO NP exerts neurotoxic effects 23 , 43 - 45 . Initially, it's important to mention that variations in the experimental results among the studies may be owed to the treatment protocols nanoparticle size and dose used, as smaller sizes of ZnO nanomaterials showed higher toxicity in treating PD-like symptoms 43 .…”
Section: Discussioncontrasting
confidence: 55%
“…Another study in 2012, explored the neuroprotective effects of ZnO NP on spatial cognition and synaptic plasticity in mice with depressive-like behaviors 32 . It is important to keep in mind that most of the research has shown conflicting findings to ours as most of the results showed the ZnO NP exerts neurotoxic effects 23 , 43 - 45 . Initially, it's important to mention that variations in the experimental results among the studies may be owed to the treatment protocols nanoparticle size and dose used, as smaller sizes of ZnO nanomaterials showed higher toxicity in treating PD-like symptoms 43 .…”
Section: Discussioncontrasting
confidence: 55%
“…In the simulation, we simulated a 0.006 mm 3 space (1000 μ m × 600 μ m × 10 μ m). We simulated the 480 invaders randomly in the space according to the previous study (Haine et al 2008) and 20, 60 and 180 blood cells according to the previous studies (2,000 - 60,000 blood cells per 1 μ L(mm 3 ) is general) (Belal and Gad 2023; Lubawy and Slocinska 2020; Kong et al 2018; Vivekanandhan et al 2022; Gao et al 2022). The simulated blood cell moved 10 μ m per 15 seconds.…”
Section: Methodsmentioning
confidence: 99%
“… 187 , 595 The primary mechanisms underlying this damage include the induction of oxidative stress, inflammation, genotoxicity, and cytotoxicity. 596 , 597 …”
Section: The Limitations/challenges Of Nanotechnology Applicationmentioning
confidence: 99%